Outcome of Preterm Neonates > 32 Weeks Gestation in Relation to Three-Tiered Fetal Heart Rate Categorization - Jelena Sabljić; Klara Čogelja; Edita Runjić; Blagoja Markoski; Marijana Barbača; Toni Modrić; Boris Bačić (Medicina)
Background and Objectives: Electronic fetal heart rate monitoring is mandatory for preterm labor. Moderate to late preterm neonates have an increased risk of overall morbidity, neonatal intensive care (NICU) admission, and consequently, medication use. The outcome of preterm neonates > 32 weeks of gestation in relation to three-tiered fetal heart rate (FHR) categorization was analyzed. Materials and Methods: This was a single-center, retrospective case-control study conducted from January 2021 to December 2023. The study included 25 FGR and 131 control cases born from 33 to 36 6/7 gestational weeks. Outcome was defined as the need for assistance after birth in first 15 min of life, respiratory outcome, and first day dopamine use and fresh frozen plasma transfusion. Maternal characteristics as risk factors for non-normal categories within three-tiered FHR categorization were also analyzed. Results: There was no significant difference in neonatal outcome among groups, except significantly lower 1 min APGAR and longer LOS in the FGR group. An increasing category within the three-tiered FHR categorization positively correlated with the need for assistance after birth, respiratory outcome, dopamine use, fresh frozen plasma transfusion, and length of hospital stay. Negative correlations were revealed between the increasing category within the three-tiered FHR categorization and first and fifth minute APGAR scores. Oligohydramnios and male sex were risk factors for non-normal categories within three-tiered FHR categorization. The correlation was tested using the Spearman correlation coefficient. A logistic regression model was employed to identify maternal risk factors for the non-normal category within three-tiered FHR categorization. All differences were statistically significant (p < 0.05). Conclusions: The increasing category within three-tiered FHR categorization may alert neonatologists to be highly suspicious of RDS, respiratory support, dopamine use, and fresh frozen plasma transfusion in neonates born from 33 to 36 6/7 gestational weeks. Oligohydramnios and male sex increase the probability for non-normal categories in the three-tiered FHR categorization.